The Relationship Between Mindfulness and Conflict Resolution Styles Among Nurse Managers: A Cross-Sectional Study - Mohammad Dar Assi MSN; Nidal F. Eshah RN, CNS, PhD; Ahmad Rayan RN, CNS, PhD (SAGE Publishing, 2022)
Introduction Mindfulness might help nurse managers in dealing with conflicts. However, the relationship between mindfulness and conflict resolution styles were still not clearly understood. Objective To identify the relationship between mindfulness and conflict resolution and to predict the conflict resolution styles of nurse managers through mindfulness. Methods A descriptive correlational cross-sectional design was employed. A convenience sample of 197 nurse managers was recruited from five public and two university hospitals. Data about nurse managers' mindfulness and conflict management styles were collected through self-reported scales. The data was collected between January and March 2020. Results Mindfulness was significantly associated with integrating ( r  = 0.31, p  < .001) and obliging ( r  = 0.14, p  = .045) conflict resolution styles. Mindfulness was able to uniquely predict using the integrating conflict resolution style (χ² = 4.65, p  = .031). Conclusions Mindfulness is uniquely related to integrating conflict resolution among nurse managers. The findings encourage stakeholders in health care organizations to develop training programs to improve managers' conflict resolution skills and to invest in managers' mindfulness.